2020
DOI: 10.1101/2020.05.27.116772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of macrophage post-translational modifications during intracellular bacterial pathogen infection

Abstract: SUMMARYMacrophages activate robust antimicrobial functions upon engulfing virulent bacteria, yet a wide array of pathogens paradoxically thrive within these innate immune cells. To probe the pathogen-macrophage interface, we used proteomics to comprehensively quantify changes in post-translational modifications (PTMs) of host proteins during infection with three evolutionarily diverse intracellular pathogens: Mycobacterium tuberculosis, Salmonella enterica serovar Typhimurium, and Listeria monocytogenes. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Integrating the results of different studies that examined different viral response regulators suggests that the transcriptional program controlling the expression of antiviral proteins such as IFN-β is likely to be comprised of several distinct modules, as the perturbation of different regulators causes distinct Mtb-related phenotypes. For example, in isolated ex vivo macrophages, disruption of CBL, TRIM14, or IRF7 alters the expression of antiviral effectors and alters the ability of a macrophage to restrict Mtb replication (45,46,67). In contrast, perturbation of RIG-I, SP140 or IFNAR has no effect on Mtb replication in isolated macrophages but profoundly alters Mtb susceptibility in mice (25,39,40,(67)(68)(69)(70).…”
Section: Antiviral Versus Antibacterial Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating the results of different studies that examined different viral response regulators suggests that the transcriptional program controlling the expression of antiviral proteins such as IFN-β is likely to be comprised of several distinct modules, as the perturbation of different regulators causes distinct Mtb-related phenotypes. For example, in isolated ex vivo macrophages, disruption of CBL, TRIM14, or IRF7 alters the expression of antiviral effectors and alters the ability of a macrophage to restrict Mtb replication (45,46,67). In contrast, perturbation of RIG-I, SP140 or IFNAR has no effect on Mtb replication in isolated macrophages but profoundly alters Mtb susceptibility in mice (25,39,40,(67)(68)(69)(70).…”
Section: Antiviral Versus Antibacterial Polarizationmentioning
confidence: 99%
“…For example, in isolated ex vivo macrophages, disruption of CBL, TRIM14, or IRF7 alters the expression of antiviral effectors and alters the ability of a macrophage to restrict Mtb replication (45,46,67). In contrast, perturbation of RIG-I, SP140 or IFNAR has no effect on Mtb replication in isolated macrophages but profoundly alters Mtb susceptibility in mice (25,39,40,(67)(68)(69)(70). This suggests that while all these pathways regulate IFN-β signaling, they might differ in their regulation of other target genes, and that these differences drive distinct physiologic states in Mtbinfected macrophages.…”
Section: Immune Response Polarizationmentioning
confidence: 99%
“…Several bacteria, including Mycobacterium tuberculosis (Mtb), Salmonella enterica serovar Typhimurium (Stm), Listeria monocytogenes (Lm), Shigella flexneri, and Legionella pneumophila (Lp), inflict phagosomal membrane damage that leads to the recruitment of Gal-3, -8, and -9 [7][8][9][19][20][21]. Previously, we found that all three of these galectins are also ubiquitylated during Mtb infection [22,23]. In addition to binding host carbohydrate, some galectins can interact directly with bacteria and their cell wall glycans [24][25][26][27], including Gal-9 binding of the Mtb cell wall polysaccharide arabinogalactan [27].…”
Section: Introductionmentioning
confidence: 99%
“…During infection, galectin recruitment and signaling promote antibacterial autophagy and bacterial growth restriction [9,15,20], proinflammatory signaling [25], and recruitment of antibacterial guanylate-binding proteins [21]. In addition, we previously found that Gal-3, -8, and -9 are all ubiquitylated during Mtb infection [26, 27], although the implications of these modifications remain unclear.…”
Section: Introductionmentioning
confidence: 99%